Media Technology Adoption in Final-Year Research: The Effects of SPSS, NVivo, and Mendeley on Research Quality, Productivity, and Time Management - Dwi Agus Kurniawan; Asrial Asrial; Maison Maison; Haryanto Haryanto (Journal of Educational Technology and Learning Creativity, 2026)
Purpose of the study: This study aimed to investigate the effects of SPSS, NVivo, and Mendeley adoption on research quality, research productivity, and time management among final-year students in higher education during the completion of research projects. Methodology: This study employed a sequential explanatory mixed methods design involving 336 undergraduate and master’s students from Universitas Jambi. Data were collected using Likert-scale questionnaires and semi-structured interviews. Quantitative data were analyzed using IBM SPSS Statistics through descriptive statistics, assumption testing, and multiple linear regression, while qualitative data were analyzed using NVivo thematic analysis. Main Findings: The findings revealed that SPSS, NVivo, and Mendeley significantly improved research quality, research productivity, and time management among final-year students. Mendeley demonstrated the strongest influence across all dependent variables, followed by SPSS and NVivo. Qualitative findings confirmed that research technologies enhanced research efficiency, improved analytical accuracy, simplified reference management, and reduced the time required to complete research activities. Novelty/Originality of this study: This study provides an integrated analysis of SPSS, NVivo, and Mendeley adoption within a single conceptual framework by examining their simultaneous effects on research quality, productivity, and time management. The study advances current knowledge by demonstrating how multiple research media technologies collectively function as strategic enablers supporting digital research performance in higher education.